The planets in our solar system - Branley, Franklyn Mansfield, 1915-2002.; O'Malley, Kevin, 1961- (New York : HarperCollins, 1998)
Describes the nine planets and other bodies of the solar system; includes directions for making models showing the size of the planets and their distance from the sun.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
5-9.
3.4
K-3
Keywords: Planets -- Juvenile literature; Planets; Planets; Solar system -- Juvenile literature; Solar system; Solar system